Company Size and Intellectual Capital on Company Value in The Consumer Goods Industry Sector Listed on The Indonesia Stock Exchange - Leny Suzan; Jihan Septiani Putri Kusworo (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Firm value is an investor's perception of the company's success in improving the welfare of investors. The company's goal is to value the company with management that can be trusted by potential investors to invest in the company. High company value indicates investor confidence with increasing stock prices. This study aims to determine the effect of firm size and intellectual capital which includes Value added capital employed, Value added human capital, Structural Capital Value added on firm value. The research uses a quantitative method approach. The research sample used was 25 companies listed on the Indonesia Stock Exchange in 2018-2020 with a 3-year period of 75 samples. The research analysis method used is panel data regression using the Eviews 12 application. Based on the results of simultaneous testing, it is known that company size and intellectual capital include Value added capital employed, Value added human capital, Structural Capital Value added has an effect on firm value. Partially Value added capital employed (VACA) has a positive effect on firm value, firm size and value added human capital (VAHU), Structural Capital Value added (STVA) has no effect on firm value.